2013
DOI: 10.1093/infdis/jit499
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Type 1—A Novel Target for Preventing Neonatal Meningitis in Mice by Escherichia coli K1

Abstract: The increasing incidence of Escherichia coli K1 meningitis due to escalating antibiotic resistance warrants alternate treatment options to prevent this deadly disease. We screened a library of small molecules from the National Institutes of Health clinical collection and identified telmisartan, an angiotensin II receptor type 1 (AT1R) blocker, as a potent inhibitor of E. coli invasion into human brain microvascular endothelial cells (HBMECs). Immunoprecipitation studies revealed that AT1R associates with endot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…coli invasion may depend partly on the AT 1 R. Moreover, this study reported that the outer membrane receptor of E . coli can induce the formation of a protein complex involving AT 1 R and the toll-like receptor 2 (TLR2) which could mediate bacteria invasion [ 42 ]. For this reason, it is possible that some similar mechanisms occur during experimental periodontitis in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…coli invasion may depend partly on the AT 1 R. Moreover, this study reported that the outer membrane receptor of E . coli can induce the formation of a protein complex involving AT 1 R and the toll-like receptor 2 (TLR2) which could mediate bacteria invasion [ 42 ]. For this reason, it is possible that some similar mechanisms occur during experimental periodontitis in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…PTx could not only up-regulate AT1R expression but also enhance AT1R-induced Ca 2ϩ influx. Interestingly, AT1R was shown to be involved in E. coli K1 RS218 invasion because inhibition of AT1R by telmisartan or siRNA-mediated knockdown abolished E. coli K1 RS218 invasion (43). Furthermore, AT1R seems to interact with gp96 and, upon binding of E. coli K1 RS218, induces Ca 2ϩ influx.…”
Section: Discussionmentioning
confidence: 99%
“…Both aminoguanidine and DAHP inhibited the onset of meningitis in 3-day-old mice by E. coli , highlighting the significance of NO production in the pathogenesis [ 79 , 121 ]. In addition, screening of a small molecule library using HBMEC invasion assays recognized Telmisartan, an angiotensin II receptor 1 (AT1R) blocker as a potent inhibitor of invasion [ 64 ]. Follow-up experiments demonstrated that AT1R forms a complex with Ecgp96 during E. coli invasion of HBMEC.…”
Section: Escherichia Coli K1-induced Neonatal Meningitismentioning
confidence: 99%